New Progress in the Combined Treatment of Traditional Chinese and Western Medicine for Oral Lichen Planus - Wang, Dan (International Journal of Public Health and Medical Research, 2024)
Oral lichen planus (OLP) is a common chronic oral mucosal disease, with a complex etiology and difficult treatment. [1] This article reviews the new progress of integrated traditional Chinese and Western medicine treatment for oral lichen planus, including Western medicine treatment methods, traditional Chinese medicine treatment concepts, specific plans for integrated traditional Chinese and Western medicine treatment, as well as their advantages and mechanisms of action. It also looks forward to future research directions.